Mitochondrial DNA Methods and Protocols - Copeland, William Chenery;Ed (Methods in molecular biology (Clifton, N.J.), v. 197., 2002)
Mutations within mitochondrial DNA (mtDNA) and the nuclear genes involved in the maintenance of mitochondrial DNA have been linked to a wide range of human diseases, including several of the most common diseases of aging. In Mitochondrial DNA: Methods and Protocols internationally recognized authorities describe in great detail the methods they have perfected to analyze mtDNA and the proteins involved in its maintenance. The analytical techniques cover the purification of mtDNA from a variety of sources and the analysis of DNA for both deletions, point mutations, and damage, for replication intermediates, and for following the fate of mtDNA outside of the mitochondria. Additional analytical methods are presented for analyzing the proteins and enzymes that maintain mtDNA. Each readily reproducible protocol includes step-by-step instructions, tips on avoiding pitfalls and extending the method to other situation, and introductory material explaining the theory behind the process. Comprehensive and timely, Mitochondrial DNA: Methods and Protocols offers both basic and clinical researchers proven cutting-edge methods for analyzing the role mtDNA plays in the aging process, apoptosis, and possibly some cancers, and for investigating the cause of mitochondrial dysfunction and disease.